Exploring the Experiences of People Treated With Immunotherapies for Advanced Melanoma and Those Caring for Them: "Real-World" Data. Issue 2 (March 2020) - Milne, Donna; Hyatt, Amelia; Billett, Alex; Gough, Karla; Krishnasamy, Mei
Abstract : Background: Recent advances in the development of immunotherapy drugs have resulted in durable responses and improved overall survival for a proportion of patients with advanced melanoma; however, toxicities can be potentially life-threatening. The patients' family and friends (carers) are relied upon to support patients at home post treatment; however, we know little about their experiences. Objectives: This study aimed to understand the experiences of patients with advanced melanoma who received immunotherapy and their carers; and to explore the impact of immunotherapy treatment on patients' and carers' quality of life (QoL). Methods: A cross-sectional, exploratory design was employed. Semi-structured interviews were conducted with patients: diagnosed with stage IV melanoma, attending an Australian public cancer hospital, had completed or were receiving treatment with immunotherapies; and the people caring for them at home. Results: Patients (n = 22) described how immunotherapy impacted emotional health, functional ability; and had damaging economic consequences. Fatigue was reported consistently as having a considerable negative influence across all domains of QoL. Carers (n = 9) were anxious about their ability to correctly identify, report and manage side effects at home. Conclusions: Results demonstrate how immunotherapy can impact the QoL of both patients and carers, either directly through toxicities or indirectly through mechanisms such as stress, financial toxicity, or fatigue that limits participation in life activities. Implications for Practice: Supportive care resources and interventions are needed for those receiving immunotherapy to minimise negative impacts on QoL. Carers likewise require better preparation and information to assist in identifying potential treatment toxicities and ensure patient safety.